The Audiovisual Proposal as a Reflection of the Influence of Social Networks on Young People: Nerve’s case - Alonso Martín-Romo, Luis; Sancho Belinchón, Celia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The behavioral tendencies of young people in the use of social networks sometimes lead to a certain assumption of roles. This fact is supported by several well-known studies. The audiovisual field, as an echo of our society, drives us to a deep reflection and also warns about the impact of the digital environment on the youth community. The purpose of this article is to address the analysis of this situation from a communicative point of view referred to the American film Nerve (2016), based on the novel ¨Nerve, a game without rules¨ written by Jeanne Ryan.